Age-related elevation of HGF is driven by the reduction of fibroblast size in a YAP/TAZ/CCN2 axis-dependent manner. Issue 1 (April 2021) - Xiang, Yaping; Qin, Zhaoping; Yang, Yan; Fisher, Gary J.; Quan, Taihao
Highlights: HGF, an anti-fibrotic factor, is elevated in aged human skin and underlying mechanisms of age-related elevation of HGF are unknown. Reduced fibroblast size, which is a prominent feature of aged skin fibroblasts in vivo, is responsible for elevated HGF. Cell size-dependent upregulation of HGF is mediated by impeded YAP/TAZ nuclear translocation and their target gene, CCN2. Elevated HGF expression is accompanied by the reduced expression of YAP/TAZ and CCN2 in the aged human skin in vivo . Age-related elevation of HGF is driven by the reduction of fibroblats size in a YAP/TAZ/CCN2 axis-dependent manner. Abstract: Background: Aged human skin is primarily attributable to the loss of collagen. Hepatocyte growth factor (HGF) acts as an anti-fibrotic factor by suppression of collagen production. In aged human skin, HGF is elevated in dermal fibroblasts and thus contributes to dermal aging (thin dermis) by suppression of collagen production. Objective: We aimed to investigate the underlying mechanisms of age-related elevation of HGF expression. Methods: Collagen fibrils in the aged skin dermis are fragmented and disorganized, which impairs collagen-fibroblast interaction, resulting in reduced fibroblast spreading and size. To explore the connection between reduced dermal fibroblast size and age-related elevation of HGF expression, we manipulate dermal fibroblast size, and cell-size dependent regulation of HGF was investigated by laser capture microdissection, immunostaining, capillary electrophoresis immunoassay, and quantitative RT-PCR. Results: We found that reduced fibroblast size is responsible for age-related elevation of HGF expression. Further investigation indicated that cell size-dependent upregulation of HGF expression was mediated by impeded YAP/TAZ nuclear translocation and their target gene, CCN2. Conversely, restoration of dermal fibroblast size rapidly reversed cell-size-dependent upregulation of HGF in a YAP/TAZ-dependent manner. Finally, we confirmed that elevated HGF expression is accompanied by the reduced expression of YAP/TAZ and CCN2 in the aged human skin in vivo . Conclusion: Age-related elevation of HGF is driven by the reduction of fibroblast size in a YAP/TAZ/CCN2 axis-dependent manner. These data reveal a novel mechanism by which reduction of fibroblast size upregulates HGF expression, which in turn contributes to loss of collagen, a prominent feature of aged human skin.